The effects of perioperative factors on early postoperative morbidity in bariatric surgery - ZENGİN, SENİYYE ÜLGEN; ORHON ERGÜN, MELİHA; GÜNAL, ÖMER (My University, 2022)
Purpose This study aims to examine the predictive role of obesity-type-related indexes and perioperative intraabdominal pressure measurements for early postoperative complications following bariatric surgery. Materials and Methods Sixty-seven female patients with obesity who underwent bariatric surgery (laparoscopic sleeve gastrectomy or gastric bypass) were included in this study. Obesity-related indexes (BMI, waist/hip ratio, and waist/height ratio) were calculated using patient data. Intraoperative hemodynamic measurements and intraabdominal pressure measurements were done at the beginning and at the end of the operation. Intraabdominal pressure measurements were done using both bladder port and trocar port. Patients were followed for early postoperative complications. Results Among 67 patients included, 22 developed early postoperative complications (32.8%), mostly pulmonary (20.9%). Trans-trocar IAP measured at the beginning of the operation emerged as the single independent predictor of postoperative complications (OR, 40.3; p=0.002). Based on ROC analysis, AUC for predicting complications was 0.955 (p<0.01). Optimal cutof point (≥14.5 mmHg) was associated with 100% sensitivity and 82% specifcity. In addition, there were weak but signifcant positive correlations between trans-trocar IAP-beginning and BMI (r=0.443, p<0.001), waist/hip ratio (r=0.434, p<0.001), and waist/height ratio (r=0.539, p<0.001). Conclusion Findings of this study suggest that a high baseline intraabdominal pressure predicts a higher risk for early postoperative complications following bariatric surgery. This information would help improve patient care. Further large studies are warranted.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Surgery; Bariatric surgery; Gastric bypass; Sleeve gastrectomy; Postoperative complication; Intraabdominal pressure; Central obesity; INTRAABDOMINAL PRESSURE; Bariatric surgery; Gastric bypass; Sleeve gastrectomy; Postoperative complication; Intraabdominal pressure; Central obesity